Lightweight Cryptographic Techniques and Cybersecurity Approaches (IntechOpen, 2023)
In the modern era of digitization, cryptographic techniques are becoming increasingly important. This book provides a comprehensive overview of lightweight cryptographic techniques for software-defined networks in the Internet of Things (IoT), cryptosystems, and the Internet of Multimedia Things (IoMT). It includes seven chapters that address such topics as image and video encryption, cybersecurity threat management, distinguishing encrypted from non-encrypted data, and more.